2019
DOI: 10.3808/jeil.201900014
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Air Dispersion of Pollutants Emitted from the Daura Oil Refinery, Baghdad- Iraq using the CALPUFF Modeling System

Abstract: The CALPUFF atmospheric transport model was used to estimate ambient air concentrations of SO2, CO, NO2, and PM2.5, in a 256 km 2 region surrounding the Daura oil refinery in Baghdad, Iraq during a six-month period in the summer for 2013 and the winter of 2014. The CALPUFF modeling system includes a meteorological processor (CALMET), a Lagrangian puff atmospheric transport model (CALPUFF), and a post processor (CALPOST). Source term and meteorological data, including surface and upper air observations, were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…When viewed as a whole from the graph in Figure 3, the pattern / trend of the concentration values with models and measurements tends to be the same. The results of this study are in line with research conducted by (Shubbar et al 2019).…”
Section: So 2 and No 2 Concentrations Calpuff Vs Field Observation Modelingsupporting
confidence: 91%
“…When viewed as a whole from the graph in Figure 3, the pattern / trend of the concentration values with models and measurements tends to be the same. The results of this study are in line with research conducted by (Shubbar et al 2019).…”
Section: So 2 and No 2 Concentrations Calpuff Vs Field Observation Modelingsupporting
confidence: 91%
“…The statistical analysis was also used to assess health based on CO Concentrations as introduced by Abbas et al, 2021 [18] who proposed a relative risk method depending on the association between diseases and exposure to air pollutants including CO. Their results indicated that CO concentrations did not exceed World human health (WHO) standards in Iraqi cities (Kirkuk, Baghdad, Al-Najaf, Al-Muthanna, and Maysan). Mahdi et al, 2020 [19] statistically evaluated the daily and monthly CO concentrations as well as weather data such IOP Publishing doi:10.1088/1755-1315/1129/1/012041 3 as temperature and solar radiation in four cities (Baghdad, Mosul, Basrah, and Rutba), results showed that the highest CO concentration was recorded in Baghdad 0.0013 kg/m3. Scientists developed a technique based on the dispersion theory of gases.…”
Section: Related Workmentioning
confidence: 99%
“…Modelling of 8 hours of CO concentration by using AERMOD dispersion model in the city of Aracaju (Macêdo & Ramos, 2020) Instead of monitoring air pollution in a city, AERMOD can be used in analyzing distribution of exhaust emission in Gas Turbine Power Plant (Zakaria, Aly & Annisa, 2020) as it is also includes gases such as SO2, NO2, CO and particulate matter (PM). CALLPUFF is another example of air quality model that can be an alternative for AERMOD to model power plant emission and also used in modelling gases emission from oil refinery process (Shubbar, Lee, Gzar, & Rood, 2019). Aside from AERMOD and CALPUFF, CFD (Kwak, Baik, Ryu, & Lee, 2015;Rivas et al, 2019) can also involve in modelling air quality.…”
Section: Related Workmentioning
confidence: 99%